P171 Efficacy and safety of upadacitinib in patients with active PsA and inadequate response to biologic DMARDs (SELECT-PsA-2): a double-blind, randomised controlled Phase III trial. (26th April 2021) - Genovese, Mark C; Lertratanakul, Apinya; Anderson, Jaclyn; Papp, Kim; Tillett, William; van den Bosch, Filip; Tsuji, Shigeyoshi; Dokoupilova, Eva; Keiserman, Mauro; Wang, Xin; Zhong, Sheng; Zueger, Patrick; et al.
Abstract: Background/Aims Upadacitinib (UPA) is a selective JAK inhibitor licensed for moderate-severe rheumatoid arthritis (RA), under evaluation for treating psoriatic arthritis (PsA). We aim to assess the efficacy and safety of UPA versus placebo (PBO) in PsA patients with prior inadequate response or intolerance to ≥ 1 biologic disease-modifying anti-rheumatic drug (bDMARD). This research was previously presented at EULAR; published in Annals of Rheumatic Diseases. Methods In SELECT-PsA-2, patients were randomised 1:1:1 to once-daily UPA 15mg (UPA15), UPA 30mg (UPA30), or PBO. Patients were stratified by baseline DMARD use, number of prior failed bDMARDs, and extent of psoriasis. Primary endpoint: the proportion of patients achieving ACR20 response at Wk12. Multiplicity controlled secondary endpoints: change in HAQ-DI, FACIT-Fatigue (FACIT-F), SF-36 Physical Component Summary (PCS) at Wk12, static Investigator Global Assessment (sIGA) of Psoriasis of 0/1 and at least a 2-point improvement from baseline, PASI75, change in Self-Assessment of Psoriasis Symptoms (SAPS) at Wk16 and proportion of patients achieving MDA at Wk24. Additional secondary endpoints: ACR50 and ACR70 at Wk12, ACR20 at Wk2. Treatment-emergent adverse events (TEAEs) reported for patients receiving ≥1 dose of study drug. Results 641 patients were randomized and received study drug; 54.3% were female with mean age of 53.4 years and mean duration since PsA diagnosis of 10.1 years, 61%, 18%, 13% of patients failed 1, 2, ≥3 bDMARD respectively. 543 (84.6%) patients completed Wk24 study drug. At Wk12, a significantly greater proportion of patients receiving UPA15 and UPA30 vs PBO achieved ACR20 (56.9% and 63.8% vs 24.1%; p < 0.0001 for both comparisons). Statistically significant improvements were observed in UPA15 and UPA30 arms vs PBO in all multiplicity controlled secondary endpoints, including ΔHAQ-DI (PBO, -0.10; UPA15, -0.30; UPA30, -0.41), ΔSF-36 PCS (PBO, 1.6; UPA15, 5.2; UPA30, 7.1), ΔFACIT-F (PBO, 1.3; UPA15, 5.0; UPA30, 6.1), and ΔSAPS (PBO, -1.5; UPA15, -24.4; UPA30, -29.7; p < .0001 for all endpoints). In addition, a greater proportion of patients achieved ACR50 and ACR70 at Wk12 with UPA vs PBO. Generally, TEAEs were reported at similar frequencies in the PBO and UPA15 arms and at a higher frequency in the UPA30 arm. Numerically higher rates of serious AEs were reported in the UPA arms. Herpes zoster was more frequent with UPA30. Three malignancies occurred in each UPA arm. One adjudicated non-fatal myocardial infarction and one adjudicated pulmonary embolism were reported with UPA15. Conclusion In this bDMARD-IR PsA population, UPA15 and UPA30 demonstrated significant improvements across PsA domains including improvements in joint and skin signs and symptoms vs PBO through Wk24, with improvement observed by Wk2. A greater percentage of patients treated with UPA achieved MDA and ACR50/70, stringent composite measures of disease control. No new safety signals were identified compared to those with UPA in RA. Disclosure M.C. Genovese: Consultancies; M.G. is a consultant for AbbVie, Eli Lilly and Company, EMD Merck Serono, Genentech/Roche, Gilead Sciences, Inc., GSK, Novartis, RPharm, Sanofi Genzyme. Grants/research support; M.G. has received grants/research support from AbbVie, Eli Lilly and Company, EMD Merck Serono, Galapagos, Genentech/Roche, Gilead Sciences, Inc., GSK, Novartis, Pfizer Inc., RPharm, Sanofi Genzyme. A. Lertratanakul: Shareholder/stock ownership; A.L. is a stock/shareholder of AbbVie Inc. J. Anderson: Shareholder/stock ownership; J.A. may be a stock/ shareholder of AbbVie Inc. K. Papp: Consultancies; K.P. is a consultant for AbbVie, Amgen, Astellas, Baxalta, Baxter, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Centocor, Dermira, Eli Lilly, Forward Pharma, Galderma, *. Member of speakers' bureau; K.P. is a member of the speakers bureau for AbbVie, Amgen, Astellas, Baxalta, Baxter, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Centocor, Dermira, Eli Lilly, Forward Pharma, Galderma *. Grants/research support; K.P. has received grants/research support from AbbVie, Amgen, Astellas, Baxalta, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Centocor, Dermira, Eli Lilly, Galderma *. Other; * & Genentech, GlaxoSmithKline, Janssen, Kyowa-Hakko Kirin, Leo Pharma, MedImmune, Merck-Serono, Merck Sharp & Dohme, Novartis, Pfizer, Regeneron, Roche, Sanofi-Genzyme, Stiefel, Takeda, UCB and Valeant. W. Tillett: Consultancies; W.T. is a consultant of AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, MSD, Pfizer Inc. & UCB. Member of speakers' bureau; W.T. is a member of the speakers bureau for AbbVie, Amgen, Celgene, Lilly, Janssen, Novartis, Pfizer Inc. & UCB. Grants/research support; W.T. has received grants/research support from AbbVie, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB. F. van den Bosch: Consultancies; F.vdB. is a consultant of AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB. Member of speakers' bureau; F.vdB. is a member of the speakers bureau for AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB. S. Tsuji: Member of speakers' bureau; S.T. is a member of the speakers bureau for AbbVie, Asahi Kasei, Chugai, Daiichi Sankyo, Eli Lilly, Eisai, Mitsubishi Tanabe, Celgene, and Novartis Pharma K.K. Grants/research support; S.T. has received grants/research support from Eli Lilly. E. Dokoupilova: Grants/research support; E.D. has received grants/research support from Eli Lilly, AbbVie, Novartis, MAURO KEISERMAN. M. Keiserman: Honoraria; M.K. has received honoraria from Pfizer, Amgen, AstraZeneca, Anthera Pharmaceuticals, Bristol-Myers Squibb, Biogen Idec Inc, Celltrion Inc., Eli Lilly, Human Genome Sciences, Novartis, Roche, Sanofi, . Member of speakers' bureau; M.K. is a member of the speakers bureau for Pfizer, Abbott, Actelion, AstraZeneca, Amgen, Roche, Bristol Myers Squibb, and Janssen. X. Wang: Shareholder/stock ownership; X.W. may be a shareholder of AbbVie Inc. S. Zhong: Shareholder/stock ownership; S.Z. may be a stock/ shareholder of AbbVie Inc. P. Zueger: Shareholder/stock ownership; P.Z. may be a stock/shareholder of AbbVie Inc. A. Pangan: Shareholder/stock ownership; A.P. may be a stock/shareholder of AbbVie Inc. P. Mease: Consultancies; P.M. is a consultant of Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB. Member of speakers' bureau; P.M. is a member of the speakers bureau for Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB. Grants/research support; P.M. has received grants/research support from Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB.